Mengembangkan Kreativitas Anak Kelompok B Usia 5-6 Tahun Melalui Kolase dengan Bahan Sintetis - Suhaela Suhaela; Muazzar Habibi; I Made Suwasa Astawa; Baik Nilawati Astini (Indonesian Publication Center, 2022)
The early childhood development period is the most appropriate period to develop all the potential possessed by early childhood. A child is an individual figure who is undergoing a development process that occurs rapidly and is fundamental to the next life process of the child. Along with the goal of early childhood education to develop all the potential possessed by children, the home is expected to be a place for children to develop attitudes, knowledge, skills, and creativity that can be used as children’s capital in adjusting to their environment and for further child development. The lack of interesting learning activities to develop creativity in children at Al-Fajri Early Childhood Education was the background of this research, so that the purpose of this study was to develop the creativity of group B children aged 5-6 years through collages with synthetic materials. This research method was development research, with three stages of development. Each of which consisted of planning, implementation, observation and development analysis stages. The subjects in this study were 7 children in group B. The data collection methods were observation and photo, documentation. Data analysis used was descriptive qualitative analysis. The result showed that collage activities could develop children’s creativity. This could be seen from the final results of the assessment of group B children scoring 46,1% in the pre-test and 91,7% inte post-test.